Qualitative analysis of 6961 free-text comments from the first National Cancer Patient Experience Survey in Scotland. Issue 6 (15th June 2017) - Cunningham, Maggie; Wells, Mary
Abstract : Objectives: To analyse free-text responses from the first Scottish Cancer Patient Experience Survey (SCPES) to understand patients' experiences of care, identify valued aspects and areas for improvement. Design: Inductive thematic analysis of seven free-text comment boxes covering all stages of the cancer experience, from a national cohort survey. Setting and participants: Adult cancer patients diagnosed across all Health Boards in Scotland between July 2013 and March 2014, and who had an inpatient stay or hospital visit between January and September 2014. 2663 respondents (of n=4835 survey respondents) provided 6961 free-text comments. Main outcome measures: Positive and negative themes of patients' experiences. Differences in the proportion of positive to negative comments by demographics. Methods: Data were analysed as follows: (1) comments were initially categorised at a high level (eg, positive, negative, miscellaneous, etc); (2) inductive codes were derived and applied to all relevant comments; (3) codes sharing similar meaning were amalgamated into subthemes, and code frequencies were measured; (4) subthemes were mapped into overarching themes; (5) difference in the proportion of positive to negative comments by demographics were analysed using χ 2 tests. Results: Participants made more positive than negative comments (1:0.78). Analysis highlighted the importance to patients of Feeling that Individual Needs Are Met and Feeling Confident Within the System . Comments also provided insight into how Processes and Structures within the system of care can negatively impact on patients' experience. Particular issues were identified with care experiences in the lead-up to diagnosis. Conclusions: This analysis provides a detailed understanding of patients' cancer care experiences, therefore indicating what aspects matter in those experiences. Although the majority of comments were positive, there were a significant number of negative comments, especially about the lead-up to diagnosis. Comments suggest patients would value greater integration of care from services involved in their treatment for cancer.